Analisis Penilaian Kinerja Karyawan Dengan Menggunakan Metode Key Performance Indicator (KPI) Pada CV. XYZ - Hesti Nurmayasari; Irwin Ananta Vidada (PT. Karya Inovatif Nusantara, 2026)
The purpose of this research is to determine the performance assessment in the company. The method currently used by the company is to carry out an evaluation process once a year, however the basis for the assessment does not yet use a structured method, so it is felt to be less effective and less in line with the company's objectives or Company Operational Standards (SOP). Then the company began to change the method for assessing employee performance, namely by using the Key Performance Indicator (KPI) method, of which only 1 division has created a KPI to determine employee performance assessment, namely the HRD Division. To overcome this, the author prepares employee performance assessments based on a method, namely the KPI method, by completing the creation of KPIs for all divisions once a month. Of the 6 Divisions, 4 Divisions with a final grade of A and 2 Divisions with a grade of B which shows that although they have succeeded in achieving most of the targets, there are still several areas that need improvement. For this reason, the KPI method can be used to solve employee performance assessment problems, so that employees can work comfortably, enthusiastically and with full motivation in carrying out their performance.